2008
DOI: 10.1645/ge-1384.1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites in Chaunus marinus and Cranopis valliceps (Anura: Bufonidae) from Lagunas Yalahau, Yucatan, Mexico

Abstract: Eight helminth taxa were found parasitizing Chaunus marinus (n = 40) and Cranopsis valliceps (n = 40) from the Parque Estatal Lagunas Yalahau, Yucatan, Mexico. Seven taxa (2 digeneans: Langeronia macrocirra, Mesocoelium monas; 1 acanthocephalan: Oncicola sp.; 3 nematodes: Rhabdias füleborni, Aplectana itzocanensis, Cruzia morleyi; and a nematode larva) were found in C. marinus, while 4 taxa (all nematodes: Rhabdias fuelleborni, Aplectana itzocanensis, Ozwaldocruzia sp., and a nematode larva) were present in C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…The widespread distribution of fi nal hosts of M. temperatus suggests the presence of a species complex which needs further research. Numerous studies have shown that in general more digeneans species are found in amphibians with either aquatic or semiaquatic habits, while nematode species are more common in terrestrial amphibians (Aho, 1990;Guillén-Hernández et al, 2000;Pérez-Ponce de León et al, 2000;Paredes-Calderón, et al, 2004;Espínola-Novelo and Guillén-Hernández, 2008). Overall, results from this work contradict these fi ndings; nematode species richness and mean abundance in L. brownorum were greater compared to that of digeneans in 2 of the localities (Table 2).…”
contrasting
confidence: 53%
“…The widespread distribution of fi nal hosts of M. temperatus suggests the presence of a species complex which needs further research. Numerous studies have shown that in general more digeneans species are found in amphibians with either aquatic or semiaquatic habits, while nematode species are more common in terrestrial amphibians (Aho, 1990;Guillén-Hernández et al, 2000;Pérez-Ponce de León et al, 2000;Paredes-Calderón, et al, 2004;Espínola-Novelo and Guillén-Hernández, 2008). Overall, results from this work contradict these fi ndings; nematode species richness and mean abundance in L. brownorum were greater compared to that of digeneans in 2 of the localities (Table 2).…”
contrasting
confidence: 53%
“…In Costa Rica (one site, n = 77 R. horribilis examined) prevalence was only 2.6% for both R. pseudosphaerocephala and R. alabialis ; mean intensity was also low: 4.5 and 1, respectively (Bursey and Brooks, 2010). In Mexico R. americanus infected 11.25% (two sites, n = 34 toads examined) of R. horribilis (Espinoza-Jiménez et al ., 2007) and prevalence of R. fuelleborni varied from 10% (one site, n = 40 R. horribilis examined, mean intensity = 1) (Espinola-Novelo and Guillen-Hernandez, 2008) to 53.3% (two sites, n = 34 R. horribilis examined) (Espinoza-Jiménez et al ., 2007) to a maximum of 66.6% (one site, n = 66 R. horribilis examined, mean intensity = 45.9) (Ruiz-Torres et al ., 2017). The latter study had comparable prevalence and intensity to the values that we report from Panama, though that study sampled only a single site.…”
Section: Discussionmentioning
confidence: 99%
“…infect R. marina across their native range (Kuzmin et al ., 2007; Dubey and Shine, 2008; Bursey and Brooks, 2010; Kuzmin et al ., 2015) and one species ( Rhabdias pseudosphaerocephala ) has been introduced to Australia (Dubey and Shine, 2008) where it negatively impacts toad growth, running performance and survival (Kelehear et al ., 2009; Kelehear et al ., 2011). In Central America, R. horribilis hosts at least four species of Rhabdias ( Rhabdias alabialis ; Rhabdias americanus ; Rhabdias fuelleborni ; R. pseudosphaerocephala ), with prevalence of infection fluctuating broadly from 2.6 to 66% (Espinoza-Jiménez et al ., 2007; Espinola-Novelo and Guillen-Hernandez, 2008; Bursey and Brooks, 2010; Ruiz-Torres et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were discovered encysted in the peritoneum of 11/49 cane toads in Mexico [ 29 ] and 2/40 cane toads had larval Oncicola sp. encysted in their mesentery in Mexico [ 30 ]. To our knowledge, the present study is the first to report any developmental stage of acanthocephalan occurring in the urinary bladder tissue of anurans [ 21 ].…”
Section: Discussionmentioning
confidence: 99%